How children solve the two challenges of cooperation. - Warneken, Felix
In this review, I propose a new framework for the psychological origins of human cooperation that harnesses evolutionary theories about the two major problems posed by cooperation: generating and distributing benefits. Children develop skills foundational for identifying and creating opportunities for cooperation with others early: Infants and toddlers already possess basic skills to help others and share resources. Yet mechanisms that solve the free-rider problem?critical for sustaining cooperation as a viable strategy?emerge later in development and are more sensitive to the influence of social norms. I review empirical studies with children showing a dissociation in the origins of and developmental change seen in these two sets of processes. In addition, comparative studies of nonhuman apes also highlight important differences between these skills: The ability to generate benefits has evolutionary roots that are shared between humans and nonhuman apes, whereas there is little evidence that other apes exhibit comparable capacities for distributing benefits. I conclude by proposing ways in which this framework can motivate new developmental, comparative, and cross-cultural research about human cooperation. -- (from the author)
Keywords: Cooperation; Fairness; Development; Evolution; Chimpanzees